The role of immune checkpoint molecules in cancers - Zhang, Meilan; Xu, Junjie; Zheng, Zhaokuan; Guo, Zhiyun; Wang, Hao; Zhou, Mingqing; Tang, Hailin; Zhu, Lewei (Frontiers in Immunology, 2026)
Immune checkpoint molecules play a central role in regulating T cell function, maintaining immune homeostasis, and facilitating tumor immune evasion, making them critical targets in cancer immunotherapy. This review provides a comprehensive overview of the structural characteristics and signaling mechanisms of key co-inhibitory and co-stimulatory molecules, and their immunoregulatory roles in both solid tumors and hematological malignancies. Recent advances in the clinical application of immune checkpoint inhibitors, combination therapy strategies, and mechanisms of resistance are discussed. Furthermore, the importance of multi-target combinatorial approaches and personalized immune modulation is emphasized, offering valuable insights and directions for optimizing cancer immunotherapy strategies.